2020
DOI: 10.1016/j.ijid.2020.06.062
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 preventive measures showing an unintended decline in infectious diseases in Taiwan

Abstract: Most of the communicable diseases have contact, airborne and/or droplet mode of transsmission. Following the outbreak of COVID-19, the Taiwan government implemented the use of masks and sanitizer, as well as other preventive measures like social distancing for prevention. This public response likely contributed significantly to the decline in the outbreak of other infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 6 publications
4
49
0
Order By: Relevance
“…The similar trends of unintended decline in other respiratory infectious diseases has already been reported from countries such as Taiwan, Singapore, and China 5 , 6 , 7 , 8 , 9 , 10 .…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The similar trends of unintended decline in other respiratory infectious diseases has already been reported from countries such as Taiwan, Singapore, and China 5 , 6 , 7 , 8 , 9 , 10 .…”
supporting
confidence: 79%
“…The similar trends of unintended decline in other respiratory infectious diseases has already been reported from other countries such as Taiwan, Singapore, and China. [5][6][7][8][9][10] Results of our study showed that the nationwide use of face mask, regular hand washing, use of sanitizers, social distancing, closure of Malls, schools, colleges, universities, bane on public gathering, massive temperature check, lockdown, extensive testing and quarantine, dramatically reduce the risk of other respiratory diseases. The use of mask is proved to be helpful not only for infectious but also for the prevention of non-infectious respiratory diseases.…”
mentioning
confidence: 99%
“…Such situations raise concerns about isolation because little information is available on transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes COVID-19, during colocation of young children with their uninfected guardians. Although children generally are asymptomatic or have mild symptoms, they could be infective (1,2). We explored whether SARS-CoV-2 was transmitted from children to their uninfected guardians in a hospital isolation setting.…”
Section: Research Lettersmentioning
confidence: 99%
“…N onpharmaceutical interventions have been shown to be effective in preventing the spread of infectious diseases. The strict compliance with nonpharmaceutical interventions implemented during the coronavirus disease (COVID-19) pandemic has been associated with a decline in influenza activity in many countries, including Taiwan (1)(2)(3)(4). Handwashing, disinfecting frequently touched surfaces, and closure of schools might also be effective against nonpolio enteroviruses (NPEV), which commonly cause a spectrum of illnesses in young populations in Asia (5).…”
mentioning
confidence: 99%
“…This was also observed in studies from China and other countries in East Asia ( 8 , 9 ). Similarly, researchers in Taiwan reported record lows of incidence rates of severe complicated influenza and IPD ( 10 ). There has not been any widespread national campaigns over the past one year to increase pneumococcal vaccination in the population, no practice changes affecting the ordering of urinary streptococcal antigen tests, and no changes in reporting requirements for IPD, to account for our findings.…”
mentioning
confidence: 96%